Hidden drop-out - Alderighi, Lorenzo,Ballatore, Rosario Maria,Tonello, Marco (Global Labor Organization (GLO), 2023)
We estimate the effects of the COVID-19 pandemic on hidden drop-out, a new measure indicating failure in achieving the minimum level of skills considered to be adequate for a student getting the high school diploma. We exploit the exogenous variation induced by the pandemic by comparing two cohorts of students (one affected and the other unaffected), within the same school. We find that hidden drop-out increases by 8.6 percentage points; the effect is stronger for students with lower levels of prior achievement, from poorer families, but also for those emotionally disrupted during assessments, and for those disclosing lower educational aspirations.
10419/272315
Keywords: Graue Literatur; hidden drop-out; secondary education; school failure; COVID-19